Incentive‐based demand response program with self‐reported baseline supported by blockchain technology. Issue 2 (11th January 2023) - Li, Bin; Banimenia, Izzeddin; Chuan, Liu; Zhansheng, Hou; Zhao, Jianli
Abstract: This research presents a decentralised incentive‐based demand response (DR) program using blockchain technology. Consumers self‐report baseline to the system operator (SO), the smart contract confirms the validity of the data to execute transactions and finally the validators record the information on the blockchain network. During the DR event, a set of consumers are randomly selected to deliver the required load reduction. The signalled consumer who delivers the load reduction is rewarded, and the non‐called consumers who diverge from their reported baseline are penalised. The randomness of choosing the consumers and penalty function restrict the baseline inflation. Here, we create a blockchain network and deploy a smart contract on the Ethereum build platform. A DR event scenario is adopted with residential houses data sets, all consumers report their baseline information to the SO through the Internet and smart meter. The SO calls four users to deliver the essential load reduction according to the probability of choosing a consumer. The smart contract verifies the received information to start transaction execution. We use proof of authority mechanism to select validation nodes from the participants using voting system. They validate each block before adding it to the blockchain. Last, the monetary transactions settle in participants' wallets. Our results confirm that decentralised systems like blockchain can significantly improve transparency, openness, and customer participation in the DR program. Also contributes to the security and privacy of user information with a minimal investment in new infrastructure. Abstract : Decentralised demand response program is established using blockchain technology. A solution for assuring the flexibility, security and transparent for energy data. Demand response events, calculate users baseline and settle rewards and penalties. Our approach is decentralised management with a minimum investment in new hardware.